2019
DOI: 10.2478/jomb-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Urinary nephrin is earlier, more sensitive and specific marker of diabetic nephropathy than microalbuminuria

Abstract: Summary Background Diabetic nephropathy (DN) is a leading cause of end-stage renal disease. Progressive damage and decline in the number of podocytes often occur in the early stages of DN. Thus, nephrin as a podocyte-specific protein may be regarded as a potential biomarker of early detection of DN. The aim of this study is to determine whether urinary nephrin is an earlier marker in DN than microalbuminuria and to test the significance of urinary nephrin as a marker for early detection of DN. Methods Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
3
32
0
2
Order By: Relevance
“…Another study also showed an association between biomarkers of podocyte damage like urinary nephrin and vascular endothelial growth factor with normoalbuminuria in patients with type 2 diabetes mellitus [ 10 ]. Urinary nephrin was found to be a sensitive and specific marker for diagnosing early diabetic nephropathy than microalbumin in another study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed an association between biomarkers of podocyte damage like urinary nephrin and vascular endothelial growth factor with normoalbuminuria in patients with type 2 diabetes mellitus [ 10 ]. Urinary nephrin was found to be a sensitive and specific marker for diagnosing early diabetic nephropathy than microalbumin in another study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies report that the expression of nephrin is reduced [ 36 , 37 ]. Studies in patients showed that the urinary excretion of nephrin can be a good marker of kidney damage since nephrinuria occurs even without albuminuria [ 40 , 41 ]. We hypothesize that the increase in the nephrin expression may represent a compensatory mechanism that allows restoring the nephrin loss through the urine, as our results showed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in this present study, biomarkers related to glomerular dysfunction such as urinary nephrin and MCP-1 had no association with mortality. Urinary MCP-1 and nephrin may be a proxy of glomerular impairment, which plays an important role in kidney diseases and has been studied in diverse scenarios [ 37 , 38 ]. The glomerular damage in COVID-19 is not common and has been described in patients with APOL1 genotypes, related to collapsing glomerulopathy in black patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%